Anticipating the hospital of the future: stakeholder perspectives on 6G technology requirements in health care - Anna Schatz; Matthias Rüb; Henriette Hegermann; Meike Hiddemann; Dario Wieschebrock; Dominik Stegemann; Jan Herbst; Christoph Lipps; Clemens Möllenhoff; Thomas Petzold; Ralf Irmer; Friedrich Köhler; et al. (International Journal of Computer Assisted Radiology and Surgery, 2026)
Abstract Purpose The ongoing 6G standardization process is largely driven by technical advancements, but with limited consideration of sector-specific needs, particularly in health care. The current scientific literature primarily focuses on technical aspects, offering minimal empirical input from healthcare professionals, patient representatives, or medical device manufacturers. This neglects clinical acceptance and applicability as a critical factor in technology adoption. The objective of this study is to explore the hopes and concerns of healthcare stakeholders in the context of 6G standardization, to support improved alignment between technological development and clinical practice. Methods To address this gap, we conducted semi-structured interviews with key healthcare stakeholders in Germany and derived recommendations for technology providers. Results The findings highlight insufficient interoperability, fragmented systems, and inadequate network coverage as central challenges in today’s daily practice. Manual documentation and data transfers further burden staff under conditions of shortage and time pressure. A robust infrastructure, particularly in rural areas where telemedicine is growing, is considered essential. Concerns persist regarding data protection and security, alongside unresolved liability for automated systems and skepticism about increasing technological dependence. Nevertheless, stakeholders see substantial opportunities in 6G for simplifying workflows, enabling seamless device integration, and supporting use cases such as real-time imaging, remote monitoring, and cross-institutional data sharing. Conclusion This study contributes to the 6G standardization by integrating the healthcare perspectives of medtech stakeholders and clinical end users, thereby supporting the development of patient-centered and clinically relevant communication solutions. The findings provide practical guidance for aligning future 6G solutions with real-world clinical requirements.